2001
DOI: 10.1577/1548-8659(2001)130<0204:mstioa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Seasonal Trophic Interactions of Adfluvial Bull Trout in Lake Billy Chinook, Oregon

Abstract: We examined the trophic interactions of bull trout Salvelinus confluentus in Lake Billy Chinook, Oregon, using a bioenergetics model combined with data on annual growth, seasonal diet, distribution, and thermal experience to determine the seasonal and size‐specific prey requirements of bull trout and the influence of bull trout predation on some of their major prey species in the reservoir. Per capita estimates of consumption were expanded to population‐level estimates based on estimates of size structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 12 publications
5
96
2
Order By: Relevance
“…The dominance of older fish suggests that the numbers of age-1 and age-2 fish were suppressed by predation (cannibalism) or that younger fish emigrate to rear in the lower mainstem East Fork Jarbidge River or tributaries. Beauchamp and Van Tassell (2001) found that bull trout of all sizes were capable of eating fusiform prey fishes of up to 50% of their own total length. They also used model simulations and field data to show that cannibalism by bull trout could remove substantial proportions of age-0 and age-1 fish, but not age-2 or older fish in Lake Billy Chinook, Oregon.…”
Section: General Catch Information and Population Characteristicsmentioning
confidence: 99%
“…The dominance of older fish suggests that the numbers of age-1 and age-2 fish were suppressed by predation (cannibalism) or that younger fish emigrate to rear in the lower mainstem East Fork Jarbidge River or tributaries. Beauchamp and Van Tassell (2001) found that bull trout of all sizes were capable of eating fusiform prey fishes of up to 50% of their own total length. They also used model simulations and field data to show that cannibalism by bull trout could remove substantial proportions of age-0 and age-1 fish, but not age-2 or older fish in Lake Billy Chinook, Oregon.…”
Section: General Catch Information and Population Characteristicsmentioning
confidence: 99%
“…As bull trout emigrate from the Metolius River into LBC at age II+ to forage their growth rates increase dramatically (Table 7.2) [Madden and Lewis 2001]. Kokanee form a large part of the bull trout diet and may explain the rapid growth at age IV+ (Beauchamp and Tassell 1999). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, kokanee (nonanadromous form of Oncorhynchus nerka), one of the main prey for overwintering bull trout [27], congregate near the dams of some hydropower reservoirs in the winter [28,29]. In Revelstoke Reservoir (British Columbia, Canada), the density of kokanee near the dam increases particularly during periods of prolonged turbine operation in the winter, possibly due to advection [29].…”
Section: Discussionmentioning
confidence: 99%